Penerapan Algoritma Fisher-Yattes Pada Aplikasi Android Seleksi Penerimaan Asisten Laboratorium - Harrizki Arie Pradana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
For the application of concepts that support facilities and places to support the learning process in which related to measurement, testing, understanding development, skills development, and innovation in the field of science in computer laboratories and laboratory assistants at the Atma Luhur ISB that meet the demands of the workforce in the field. In the process of screening a new laboratory assistant is one of the steps in the laboratory so that prospective assistants are selected according to specified criteria. But unfortunately, the lack of information efficiency towards the acceptance of new laboratory assistants for active students requires a new mobile-based Assistant Admissions System where prospective assistants can carry out the entire registration process quickly. This application was created using the waterfall model and object-oriented methods with UML Tools. Registration application for laboratory assistants makes it easy to access registration for students and is made to apply the Fisher Yattes algorithm in the process of randomizing questions in the online test process, The Advantages of Fisher-Yates Algorithm is the effectiveness of the randomization method and the optimal complexity of the algorithm, O (n). Then it can be concluded that the planning of the acceptance system for android-based computer laboratory assistant candidates can maximize activities in serving prospective laboratory assistants to register and enter the online selection test.